STUDY OF ANTIMICROBIAL, ANALGESIC AND ANTICONVULSANT ACTIVITY OF NOVEL ISATIN DERIVATIVES - Chirra, Sravanthi; Rao Jupally, Venkateshwar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Isatin is an endogenous compound and possess a wide variety of biological activities. In the present investigation, a different isatin derivatives such as novel isatin 3-[N-(4-substituted)-hydrazinyl-3-oxo prop 1-en-2yl) benzamides and their antimicrobial, analgesic and anticonvulsant activity was evaluated in different animal models. Antimicrobial activity by cup plate agar diffusion method. The analgesic activity was measured by Eddy’s hot plate method, and reaction time was recorded when the animals licked their for and hind paws and jumped at before 0 hr, 0.5 hr, 1 hr and 2 hrs after administration of test drugs. 4-aminopyridine chemical induction method was employed for anticonvulsant activity. All the compounds were screened, among the screened compounds some compounds showed antimicrobial, analgesic and anticonvulsant activity with dose-dependent effect when compared with the control group. Keywords: Isatin, Antibacterial, Antifungal, Analgesic, Anticonvulsant activity.